Growth and nutrient absorption by Raisa tomato cultivar grown in hydroponic system/ Crescimento e marcha de absorção de nutrientes em tomateiro cultivar Raísa cultivado em sistema hidropônico - Arthur Bernardes Cecílio Filho (Semina: Ciências Agrárias, 2011)
The production and quality of tomatoes has increased with the emergence of new genotypes and cropping systems such as hydroponics, however, there are few studies on the nutrition of plants. The objective was to evaluate the growth and motion of absorption of nutrients by Raisa tomato cultivar, grown in hydroponic system. The experimental design was randomized blocks with eight treatments consisting of the times of sampling: 15, 25, 35, 45, 55, 65, 75 and 85 days after transplanting (DAT) and five replications. The tomato seedlings were transplanted to pots of 8 dm3 (on 31-03-2008), filled with the base substrate of coconut fiber, constantly irrigated with Hoagland and Arnon nutrient solution. During the experimental period and focuses on the development of plants and dry leaves, stems, fruits and roots. The dry matter accumulation of leaves and roots of tomato cultivar Raisa was relatively faster than the national stem and fruit, over cultivation, with predominance of dry fruits (45%) on the leaves (27%), the stem (24%) and roots (3%) at the end of the cycle. The accumulation of nutrients and micronutrients by the tomato cultivar Raisa was fit with linear increase throughout the cultivation, except for Mn which was quadratic. Most of the tomato nutritional requirement for nutrients was K, N and Ca and micronutrients was Fe, Zn and Mn. A produção e a qualidade do tomate têm aumentado com o surgimento de novos genótipos e sistemas de cultivo como o hidropônico, entretanto, são poucas as pesquisas sobre a nutrição das plantas. Assim, a presente pesquisa teve o objetivo de avaliar o crescimento e a marcha de absorção de nutrientes pelo tomateiro cultivar Raísa, cultivado em sistema hidropônico. O delineamento experimental adotado foi em blocos casualizados com oito tratamentos constituídos pelas épocas de amostragem: 15; 25; 35; 45; 55; 65; 75 e 85 dias após o transplante (DAT) e cinco repetições. As mudas de tomateiro foram transplantas para vasos de 8 dm3, preenchido com substrato a base de fibra de coco, constantemente irrigadas com solução nutritiva de Hoagland e Arnon. Durante o período experimental, avaliou-se o desenvolvimento das plantas e a matéria seca de folha, caule, frutos e raízes. O acúmulo de matéria seca de folhas e raízes do tomateiro cultivar Raísa foi relativamente mais rápido que os órgãos caule e frutos, ao longo do cultivo, havendo predomínio da matéria seca de frutos (45%) em relação às folhas (27%), ao caule (24%) e às raízes (3%) no final do ciclo da cultura. O acúmulo de macronutrientes e de micronutrientes pelo tomateiro cultivar Raísa teve incremento com ajuste linear ao longo do cultivo, exceto o Mn que foi quadrático. A maior exigência nutricional do tomateiro para os macronutrientes foi K, N e Ca e dos micronutrientes foi Fe, Zn e Mn.